2009
DOI: 10.1007/s00296-009-1152-8
|View full text |Cite
|
Sign up to set email alerts
|

Lung involvement in patients with primary Sjögren’s syndrome: what are the predictors?

Abstract: The aim of this study was to investigate the prevalence, predictors and radiological findings of primary Sjögren's syndrome (pSS)-associated lung involvement. This retrospective cohort study included 123 patients with demographic, clinical, laboratory and radiological data who were diagnosed with pSS. Lung involvement was defined based on the presence of pulmonary signs/symptoms and/or impaired pulmonary function tests along with alterations in high-resolution computerized tomography (HRCT). Thirty patients (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 25 publications
5
70
5
1
Order By: Relevance
“…At the beginning of the study, changes were observed only in 6% of patients and after 75 months the percentage increased to 15%. The mean total ESSDAI score for this domain was low (2)(3)(4)(5). Older patients at the time of diagnosis (> 70 years) were less active during follow-up, but had a higher pulmonary activity score.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…At the beginning of the study, changes were observed only in 6% of patients and after 75 months the percentage increased to 15%. The mean total ESSDAI score for this domain was low (2)(3)(4)(5). Older patients at the time of diagnosis (> 70 years) were less active during follow-up, but had a higher pulmonary activity score.…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence of respiratory symptoms in pSS varies a lot (9-75%), depending on the publications and assessment methods (clinical symptoms, chest X-ray, computed tomography). 2 High Resolution Computed Tomography (HRCT) is a relatively noninvasive method and is currently the most important method for detecting early lung parenchymal abnormalities and reduced lung function. Common HRCT findings of pSS in the lungs include ground-glass attenuation, bronchiectasis, a reticular pattern and honeycomb appearance.…”
mentioning
confidence: 99%
“…ILD is the most common complication of pSS and the incidence of ILD varied in many studies. 18,26,27 The clinical diagnosis of pSS-ILD is somewhat difficult, because the majority of patients lack specific respiratory symptoms. Diagnostic approaches for pSS-ILD include: (i) chest X-rays; (ii) pulmonary function tests; (iii) HRCT; (iv) bronchoalveolar lavage; (v) nuclide examination; and (vi) lung biopsy, which are the gold standard for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The number of new cases from 1999 to 2012 was 3,7,7,7,12,15,15,11,26,33,43,46, 58 and 32, respectively, which showed a gradual upward trend (Fig. 1).…”
Section: Characteristics Of Patientsmentioning
confidence: 98%
“…Females are also prone to other autoimmune diseases as well (6,15,27,28). We think that both CTD and CTD-OLD are more frequent in females.…”
Section: Discussionmentioning
confidence: 91%